Determination of trace metals in palm oil plantation soil and its potential risk towards human health / Nur Fatihah Abdul Rahman - Abdul Rahman, Nur Fatihah (Faculty of Health Sciences, 2015)
Introduction: Trace metals are naturally available in soil which important for plant growth and development. However its content may increase due to application of agriculture chemicals. Its concentration in soil is influence by certain condition such soil’s type, pH, and organic matter content. Increase of the concentration of trace metal is become a concern especially when it may give potential health risk. In this study, concentration of four trace metals was determined in palm oil soil plantation at Pasir Salak, Perak. Objective: To identify the concentration of trace metals in palm oil soil and its potential risk towards human health. Methodology: A total of 100 soil samples were randomly collected from two sites namely site A and site C and were sent to the laboratory for further analysis. Graphite Furnace Atomic Absorption Spectrometry (GFAAS) was used for the analysis of trace metal (Cadmium, Chromium, Iron and Potassium) concentration. Results: The concentration of Cadmium, Chromium and Potassium at both sites was found higher than typical range of natural occurrence of metals concentration of CLMC Guideline except for Iron which indicates those trace metal input come from other sources other than natural occurrence. The mean’s value for cadmium is 0.58 mg/kg, chromium, 17.90 mg/kg, potassium 69.17 mg/kg and iron 709.78 mg/kg. While comparing the concentration with Environmental Protection Act 2009, about 6 sampling point for site C have concentration value above the limit for cadmium and only one sampling point for site A. As for chromium, all the results are complying. By referring Canadian Soil Quality Guidelines 2007, the reading concentration for cadmium and chromium showing above the limit only for one sampling point at site A and one sampling point at site B. Meanwhile, for health risk assessment, the sum of Hazard Quotient (HQ) for three exposure routes (ingestion, inhalation and skin contact) which is Hazard Index (HI) for offsite residents, outdoor workers and construction workers is below than 1 (HI<1). This shows that there is low or no potential health risk. Conclusion: Based on the study, the concentrations of trace metals are safe to human health and further research need to be done to further understand the effects of trace metals to human health via soil as exposure pathway.